Suicide and Life Insurance. Issue 1 (January 2022) - Berman, Alan L.; Silverman, Morton M.; Wortzel, Hal S.; McIntosh, John L.
Abstract : Much has been written about the history of suicide and, notably, about societies that condemned both the act and the actor, resulting in a perpetuation of suicide being stigmatized in many cultures. One aspect of this perceived stigmatization involves exclusionary clauses in life insurance policies that reject paying benefits to survivor-beneficiaries of the decedent if the decedent has died by suicide within a prescribed time frame. From the perspective of the individual, life insurance is designed to protect the estate of a decedent from a significant financial burden. From the insurer's perspective, there are essentially 2 reasons for having a suicide exclusion clause: limiting risk and preventing or discouraging fraud. This column examines these rationales in light of the estimated few suicides that do occur during exclusionary clause time frames. Observations are made about the effect of these clauses on those impacted by the loss of a loved one who died by suicide within the exclusionary time frame. An examination of the perspectives of both the life insurance industry and the impacted survivors of suicide decedents raises questions about what are reasonable and appropriate exclusionary clause time frames that protect both the insurer and survivor-beneficiaries. The forensic expert consulting on such cases should be cognizant of these competing perspectives and engage in therapeutic assessment whenever possible, identifying opportunities to promote thoughtful suicide postvention.